2021
DOI: 10.1002/mbo3.1196
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression during growth on model and commercial mixtures of naphthenic acids in Pseudomonas fluorescens Pf‐5

Abstract: Naphthenic acids (NAs) are carboxylic acids with the formula (C n H 2n + Z O 2 ) and are among the most toxic, persistent constituents of oil sands process‐affected waters (OSPW), produced during oil sands extraction. Currently, the proteins and mechanisms involved in NA biodegradation are unknown. Using LC‐MS/MS shotgun proteomics, we identified proteins overexpressed during the growth of Pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 103 publications
1
3
0
Order By: Relevance
“…This may have been a limitation of using duplicates for the transcriptome studies, but the use of transcriptional lux fusions validated many of the upregulated genes identified by RNA-seq. Many fatty acid degradation genes that likely contribute to β-oxidation of naphthenic acids were identified, which is consistent with the results of a proteomic study with Pseudomonas fluorescens Pf-5 (53). This study identified transcriptional repressors that may act as naphthenic acid sensing proteins.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This may have been a limitation of using duplicates for the transcriptome studies, but the use of transcriptional lux fusions validated many of the upregulated genes identified by RNA-seq. Many fatty acid degradation genes that likely contribute to β-oxidation of naphthenic acids were identified, which is consistent with the results of a proteomic study with Pseudomonas fluorescens Pf-5 (53). This study identified transcriptional repressors that may act as naphthenic acid sensing proteins.…”
Section: Discussionsupporting
confidence: 86%
“…We identified several strong inducible promoters capable of NA sensing, driving the expression of genes involved in degradation or protection from NA. A transcriptome approach was used for the discovery of NA-induced genes, although there were relatively few significantly induced genes when exposed to various NA extracts, compared to other genomic studies (53). This may have been a limitation of using duplicates for the transcriptome studies, but the use of transcriptional lux fusions validated many of the upregulated genes identified by RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Naphthenic acids present as pollutants in oil sand tailings ponds are a series of aliphatic and alicyclic carboxylic acids with a pKa in the 5-6 range so at the pH of oil sands (approximately 8) these compounds are generally negatively charged but also vary significantly in their degree of hydrophobicity [25,27,29]. In these studies, we used a more aromatic naphthyloxy butanoic acid and a more complex mixed aliphatic/aromatic compound often used in oil sands naphthenic acid toxicity studies, butyl phenyl butanoic acid [51,52]. Naphthenic acids pollutants are present in oil sands tailings ponds at up to 120 µg/mL concentrations [53,54] and so in these binding studies the naphthenic acids were used at similar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…metagenomics, metatranscriptomics) to scan the degradation potential of unculturable microorganisms. Experiments targeting gene or protein expression analyses (McKew et al 2021 ) have so far provided important insight on the diversity of NA-degrading microorganisms, genes, and pathways. This, coupled with the ever-growing accumulation of sequence data, provides the opportunity to explore the NA degradation potential in a range of environments where metagenomic data is available.…”
Section: Future Researchmentioning
confidence: 99%